Editors’ Introduction: Learning, Adaptation, and Fragile Social Orders across Asian and Adjacent Worlds - Asep Iqbal (Centre for Asian Social Science Research (CASSR), Faculty of Social and Political Sciences, UIN Sunan Gunung Djati Bandung, 2022)
Journal of Asian Social Science Research, Volume 4, Number 2, 2022, brings together five articles that ask how people and institutions respond when familiar arrangements become unsettled. The issue moves across South Africa, Bangladesh, Indonesia, Lombok, and the Maldives. Its geographical range extends beyond Asia in the opening article, but its intellectual concern remains consistent with the journal’s broader mission: to understand social life comparatively, carefully, and with attention to human experience. The word that best captures this issue is not crisis, though crisis is present. It is adaptation. Students adapt to new freedoms and risks. Educational institutions adapt to online learning during the COVID-19 pandemic. Communities adapt local resources into new forms of collective action. Religious traditions adapt through historical encounter and social negotiation. Democratic institutions adapt, or fail to adapt, under domestic instability and regional influence. In each case, adaptation is not automatic. It is shaped by infrastructure, personality, gender, history, leadership, belief, community networks, and power.